2008
DOI: 10.1111/j.1551-2916.2007.02169.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressureless Sintering of Zirconium Diboride: Particle Size and Additive Effects

Abstract: Zirconium diboride (ZrB 2 ) was densified by pressureless sintering using o4-wt% boron carbide and/or carbon as sintering aids. As-received ZrB 2 with an average particle size of B2 lm could be sintered to B100% density at 19001C using a combination of boron carbide and carbon to react with and remove the surface oxide impurities. Even though particle size reduction increased the oxygen content of the powders from B0.9 wt% for the as-received powder to B2.0 wt%, the reduction in particle size enhanced the sint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
192
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(197 citation statements)
references
References 30 publications
5
192
0
Order By: Relevance
“…Chamberlain et al [68] produced a ZrB 2 ceramic without sintering aids that reached 98 pct theoretical density but required 9 hours pressureless sintering at 2423 K (2150°C). Fahrenholtz et al [69] found that ZrB 2 could not be sintered pressurelessly without the presence of a sintering aid (in this case a combination of B 4 C and C), which reacts with and removes oxygen impurities from the surface of the diboride powders. A~100 pct dense material was formed at 2173 K (1900°C) with B 4 C and C present as sintering aids.…”
Section: Densification Methodsmentioning
confidence: 99%
“…Chamberlain et al [68] produced a ZrB 2 ceramic without sintering aids that reached 98 pct theoretical density but required 9 hours pressureless sintering at 2423 K (2150°C). Fahrenholtz et al [69] found that ZrB 2 could not be sintered pressurelessly without the presence of a sintering aid (in this case a combination of B 4 C and C), which reacts with and removes oxygen impurities from the surface of the diboride powders. A~100 pct dense material was formed at 2173 K (1900°C) with B 4 C and C present as sintering aids.…”
Section: Densification Methodsmentioning
confidence: 99%
“…It has been reported for different systems that particle size plays a role in densification. 17 Refinement and homogenization of powder particles together with activation of their surfaces causes intensification of shrinkage processes during sintering. Besides this, some previous studies have shown that the reduction of particle size plays a role by shifting the sintering temperature to a lower value, 17 which can be important for sintering samples containing metal borides with relatively low melting points.…”
Section: Effect Of Short-term Ball Milling and Densitymentioning
confidence: 99%
“…To improve the sintering densification of ZrB 2 , very high sintering temperatures (2100°C-2300°C), pressure-assisted sintering procedures, and sintering additives are usually adopted. So far, a lot of metals (e.g., Cr and Fe) and ceramic powders (e.g., Si 3 N 4 , AlN, WC, and MoSi 2 ) were used to promote the sinterability of ZrB 2 [7][8][9][10][11]. MoSi 2 was found to be an effective additive to improve both sinterability and oxidation resistance of ZrB 2 ceramics [12][13][14].…”
Section: Introductionmentioning
confidence: 98%